Impact of non-communicable disease multimorbidity on health service use, catastrophic health expenditure and productivity loss in Indonesia: a population-based panel data analysis study. Issue 2 (17th February 2021) - Marthias, Tiara; Anindya, Kanya; Ng, Nawi; McPake, Barbara; Atun, Rifat; Arfyanto, Hafiz; Hulse, Emily SG; Zhao, Yang; Jusril, Hafizah; Pan, Tianxin; Ishida, Marie; Lee, John Tayu
Abstract : Objectives: To examine non-communicable diseases (NCDs) multimorbidity level and its relation to households' socioeconomic characteristics, health service use, catastrophic health expenditures and productivity loss. Design: This study used panel data of the Indonesian Family Life Survey conducted in 2007 (Wave 4) and 2014 (Wave 5). Setting: The original sampling frame was based on 13 out of 27 provinces in 1993, representing 83% of the Indonesian population. Participants: We included respondents aged 50 years and above in 2007, excluding those who did not participate in both Waves 4 and 5. The total number of participants in this study are 3678 respondents. Primary outcome measures: We examined three main outcomes; health service use (outpatient and inpatient care), financial burden (catastrophic health expenditure) and productivity loss (labour participation, days primary activity missed, days confined in bed). We applied multilevel mixed-effects regression models to assess the associations between NCD multimorbidity and outcome variables, Results: Women were more likely to have NCD multimorbidity than men and the prevalence of NCD multimorbidity increased with higher socioeconomic status. NCD multimorbidity was associated with a higher number of outpatient visits (compared with those without NCD, incidence rate ratio (IRR) 4.25, 95% CI 3.33 to 5.42 for individuals with >3 NCDs) and inpatient visits (IRR 3.68, 95% CI 2.21 to 6.12 for individuals with >3 NCDs). NCD multimorbidity was also associated with a greater likelihood of experiencing catastrophic health expenditure (for >3 NCDs, adjusted OR (aOR) 1.69, 95% CI 1.02 to 2.81) and lower participation in the labour force (aOR 0.23, 95% CI 0.16 to 0.33) compared with no NCD. Conclusions: NCD multimorbidity is associated with substantial direct and indirect costs to individuals, households and the wider society. Our study highlights the importance of preparing health systems for addressing the burden of multimorbidity in low-income and middle-income countries.